Pengaruh Brand Image, Lifestyle Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Customer Billphone Malang - Muhammad Farhan; Muhammad Mansur; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In this research, the researcher aims to determine the existence of influence brand image, lifestyle and quality product on purchasing di decisions. This type of research used is quantitative research. The data collection method in this study is primary data obtained from distributing questionnaires to respondents. The population in this study used non-probability sampling which was obtained from the number of consumers who bought Iphone products at Billphone Malang from February to July 2023 as many as 215 consumers. The sampling technique in this study was purposive sampling with the slovin method and a total sample of 68 respondents who had made purchases at Billphone Malang was obtained. The data analysis method used in this study is multiple linear regression analysis. Based on the research results obtained by researchers that partially brand image influences purchasing decisions, lifestyle influences purchasing decisions and product quality influences purchasing decisions of Malang Billphone customers. Meanwhile, it was simultaneously found that brand image, lifestyle and product quality had an influence on the purchasing decisions of Billphone Malang customers.  Keywords :Brand Image, Lifestyle, Product Quality and Buying Decision